Differential expressions of HSP70 gene between golden and brown noble scallops Chlamys nobilis under heat stress and bacterial challenge. Issue 94 (November 2019) - Cheng, Dewei; Liu, Hongxing; Zhang, Hongkuan; Soon, Tan Kar; Ye, Ting; Li, Shengkang; Ma, Hongyu; Zheng, Huaiping
Abstract: Heat shock proteins (HSPs) are a family of conserved proteins that enhance stress resistance and protect cells from external damage. In the present study, the full-length HSP70 cDNA from the noble scallop Chlamys nobilis (designated CnHSP70 ) was first cloned and characterized. Then, the expression of CnHSP70 in golden and brown scallops with different carotenoid content was evaluated under heat stress and Vibrio parahaemolyticus challenge. The complete CnHSP70 cDNA is 2621 bp, including a 1971 bp open reading frame (ORF) encoding a polypeptide of 656 amino acids with an estimated molecular weight of 71.55 kDa and an isoelectric point of 5.32. Based on amino acid sequence and phylogenetic analysis, the CnHSP70 gene was identified as a member of the cytoplasmic HSP70 family. The CnHSP70 was ubiquitously expressed in all examined tissues, including intestines, hemocytes, mantle, adductor and gills, with the highest expression in gills. After heat stress and V. parahaemolyticus injection, the expression levels of CnHSP70 in gills and hemocytes of golden and brown scallops were both significantly increased, indicating that the gene was involved in resistance or immune response. Moreover, under both conditions, similar expression profiles of CnHSP70 were observed between gills and hemocytes from the same color scallop, but different expression levels were detected in the same tissue from the different color scallop, which may be related to difference in their carotenoids content. Highlights: This is the first report comparing the HSP 70 in polymorphic noble scallops. Heat stress and bacteria challenge can induce the up-regulation of HSP70 in noble scallop. Brown scallops were more sensitive than golden scallops to the heat and bacterial stress. Different HSP70 expressions existed between golden and brown scallops to the heat and bacterial stress.